Answer:
a = (x - b)/2
Step-by-step explanation:
2a + b = x
-b -b
2a = x - b
/2 /2
a = (x - b)/2
for ex:
x = 3
b = 2
a = ((3) - (2))/2 = 0.5
a = 0.5
2a + b = x
2(0.5) + 2 = 3
Answer:
30%
Step-by-step explanation:
if 60% were thin mint and 10% were Samoas that is 70% of cookies. remaining 30% must be trefoils. hope this helps
Answer: see proof below
<u>Step-by-step explanation:</u>
![\dfrac{1+\sec A}{\sec A}=\dfrac{\sin^2 A}{1-\cos A}](https://tex.z-dn.net/?f=%5Cdfrac%7B1%2B%5Csec%20A%7D%7B%5Csec%20A%7D%3D%5Cdfrac%7B%5Csin%5E2%20A%7D%7B1-%5Ccos%20A%7D)
Use the following Identities:
sec Ф = 1/cos Ф
cos² Ф + sin² Ф = 1
<u>Proof LHS → RHS</u>
![\text{LHS:}\qquad \qquad \dfrac{1+\sec A}{\sec A}](https://tex.z-dn.net/?f=%5Ctext%7BLHS%3A%7D%5Cqquad%20%5Cqquad%20%5Cdfrac%7B1%2B%5Csec%20A%7D%7B%5Csec%20A%7D)
![\text{Identity:}\qquad \qquad \dfrac{1+\frac{1}{\cos A}}{\frac{1}{\cos A}}](https://tex.z-dn.net/?f=%5Ctext%7BIdentity%3A%7D%5Cqquad%20%5Cqquad%20%5Cdfrac%7B1%2B%5Cfrac%7B1%7D%7B%5Ccos%20A%7D%7D%7B%5Cfrac%7B1%7D%7B%5Ccos%20A%7D%7D)
![\text{Simplify:}\qquad \qquad \dfrac{\frac{\cos A+1}{\cos A}}{\frac{1}{\cos A}}\\\\\\.\qquad \qquad \qquad =\dfrac{1+\cos A}{1}](https://tex.z-dn.net/?f=%5Ctext%7BSimplify%3A%7D%5Cqquad%20%5Cqquad%20%5Cdfrac%7B%5Cfrac%7B%5Ccos%20A%2B1%7D%7B%5Ccos%20A%7D%7D%7B%5Cfrac%7B1%7D%7B%5Ccos%20A%7D%7D%5C%5C%5C%5C%5C%5C.%5Cqquad%20%5Cqquad%20%5Cqquad%20%3D%5Cdfrac%7B1%2B%5Ccos%20A%7D%7B1%7D)
![\text{Multiply:}\qquad \qquad \dfrac{1+\cos A}{1}\cdot \bigg(\dfrac{1-\cos A}{1-\cos A}\bigg)\\\\\\.\qquad \qquad \qquad =\dfrac{1-\cos^2 A}{1-\cos A}](https://tex.z-dn.net/?f=%5Ctext%7BMultiply%3A%7D%5Cqquad%20%5Cqquad%20%5Cdfrac%7B1%2B%5Ccos%20A%7D%7B1%7D%5Ccdot%20%5Cbigg%28%5Cdfrac%7B1-%5Ccos%20A%7D%7B1-%5Ccos%20A%7D%5Cbigg%29%5C%5C%5C%5C%5C%5C.%5Cqquad%20%5Cqquad%20%5Cqquad%20%3D%5Cdfrac%7B1-%5Ccos%5E2%20A%7D%7B1-%5Ccos%20A%7D)
![\text{Identity:}\qquad \qquad \dfrac{\sin^2 A}{1-\cos A}](https://tex.z-dn.net/?f=%5Ctext%7BIdentity%3A%7D%5Cqquad%20%5Cqquad%20%5Cdfrac%7B%5Csin%5E2%20A%7D%7B1-%5Ccos%20A%7D)
![\text{LHS = RHS:}\quad \dfrac{\sin^2 A}{1-\cos A}=\dfrac{\sin^2 A}{1-\cos A}\quad \checkmark](https://tex.z-dn.net/?f=%5Ctext%7BLHS%20%3D%20RHS%3A%7D%5Cquad%20%5Cdfrac%7B%5Csin%5E2%20A%7D%7B1-%5Ccos%20A%7D%3D%5Cdfrac%7B%5Csin%5E2%20A%7D%7B1-%5Ccos%20A%7D%5Cquad%20%5Ccheckmark)